Diseño de personajes a partir de los saberes ancestrales para generar valor identitario en la parroquia San Buenaventura de la ciudad de Latacunga - Almachi Lema, Jessica Elizabeth (2020)
The decline of the ancestral medicine due to the technological advances of the modern medicine devalues and breaks the native knowledge of the healers that perform the art of cleaning with the guinea pig and medicinal herbs, therefore, the present project has as objective to strengthen the traditions and ancestral knowledge of the parish of San Buenaventura of the city of Latacunga by means of the creation of illustrated characters of the place applied in an artbook. The research techniques were applied: field, scientific, experimental and explanatory, also analyzed and interpreted theoretical and graphic information. In the design process, the biographical interpretative method and Bruce Archer's design methodology were used. Archer mentions the following phases: analytical phase, creative phase and executive phase, which in turn is subdivided into: problem definition, obtaining relevant data, analysis and synthesis, prototype development, preparation and execution. The research data resulted in the structure of a design product containing plants and illustrated characters that tells the story of one of the most recognized healers of the parish of San Buenaventura in the city of Latacunga. Finally, it was concluded with several arguments that show the ancestral medicine as an alternative and economic healing method, practiced by healers from neighboring towns to the civilization. Then, a workflow was organized and the project was implemented.